Respuesta :

Answer:

f(-2) = -12

Step-by-step explanation:

f(x) = 2 • 3x.

Let x = -2

f(-2) = 2* 3(-2)

      = -12

Answer:

f(-2)=-12

Step-by-step explanation:

This question asks us to find f(-2). This means we need to find out what f(x), or y is, when x is equal to -2.

f(x)=2*3x

Therefore, we can substitute -2 in for every x.

f(-2)=2*3(-2)

Solve according to PEMDAS (Parentheses, Exponents, Multiplication, Division , Addition, Subtraction)

Multiply 3 and -2 first

f(-2)=2*-6

Multiply 2 and -6

f(-2)= -12

ACCESS MORE